A prospective observational study on tolerance and satisfaction to hepatic haemodynamic procedures. (27th March 2014) - Casu, Stefania; Berzigotti, Annalisa; Abraldes, Juan G.; Baringo, M. Angels; Rocabert, Laura; Hernández‐Gea, Virginia; García‐Pagán, Joan Carles; Bosch, Jaume
Abstract Background Understanding patients' attitudes to clinical experiences is essential for developing high‐quality patient‐centred healthcare, as a better knowledge of patients' tolerance and satisfaction might allow implementing measures that ameliorate comfort, care and use of resources. Aims We aimed to describe patients' tolerance and satisfaction to invasive hepatic haemodynamic procedures, and to investigate which factors might influence patients' perspective in this field. Methods Visual Analogue Scale (VAS) questionnaires regarding pain and duration (for tolerance), and comfort and general handling (for satisfaction) were prospectively administered to all consecutive patients (N = 327) submitted to hepatic haemodynamic procedures (N = 355) in a tertiary care setting during 2011. VAS scores ranged between 0 and 100 mm and items were defined as excellent if <10 mm; good if 10–20 mm and inadequate if >20 mm. Clinical and laboratory data were also collected. Results Satisfaction was excellent in >95% of cases (mean 2 ± 5 mm, median 0 mm) and average tolerance was good (15 ± 18 mm; median 6 mm). A percentage of 59% of patients had excellent tolerance, 9% good and 32% had inadequate tolerance. Duration and complexity of the procedure and limited operator's experience were associated with inadequate tolerance on univariate analysis; duration of the procedure remained the only independent factor associated with inadequate tolerance on multivariate analysis. Procedures lasting <35 min had a >80% probability of being well tolerated. Conclusions Satisfaction and tolerance to hepatic haemodynamic procedures are excellent and good respectively. Tolerance was decreased in long procedures; hence reducing as much as possible the duration of the procedures might further improve tolerance.